Utilização de resíduos do processamento mecânico da madeira para a fabricação de chapas de partículas aglomeradas - Dacosta, Lourdes Patricia Elias (2004)
The objective of this work was to investigate the quality of particleboard manufactured with residue of slash pine, coming from the wood mechanical processing. The boards were produced with two types of residues, hammermilled sawmill headrig chips and planer shavings, used pure or mixed. The adhesive used was urea-formaldehyde resin in proportions of 4, 8 and 12% (based on ovendry weight of wood particles) and nominal densities were 0,6 and 0,7 g/cm3. There were evaluated the bending properties, internal bond, screw withdrawal, water absorption and thickness swelling. The results indicated that the bending properties increased with the proportion of maravalha, with the board density and adhesive content. Internal bond and screw withdrawal values were larger using adhesive content between 8 and 12% and larger density of the boards, independent of the type of the residue. For water absorption, using adhesive content between 8 and 12%, larger nominal board density and planer shavings, the values were smaller. The same behaviour was observed in relationship to thickness swelling of the boards. Observing the results it was possible to conclude that using planer shavings, combined with larger proportions of adhesive and board density, adequate panel can be produced.